Analysis of Factors Influencing Interest in Purchasing Porang Rice Using The Extended Theory of Planned Behavior (E-TPB) - Annisa, Amalia Widya; Aziz, Ibnu Wahid Fakhrudin; Suharno, Suharno (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
Porang rice, as imitation rice made from porang tubers, can be used as a substitute for white rice because it contains low calories and high fiber. In Indonesia, the marketing of porang rice and related research is still limited. This research aims to determine the characteristics of respondents and the factors that influence interest in buying porang rice, as well as recommendations for marketing strategies based on the research results. Data were analyzed using descriptive statistics, chi-square test, and SEM-PLS. The sample used was selected using a non-probability sampling method using a purposive sampling technique. The number of respondents obtained was 112 respondents. The research results found that the knowledge and status of respondents who were on a calorie diet were the main characteristics of respondents regarding their interest in buying porang rice. Subjective norms and perceived behavioral control directly influence interest in buying porang rice. Product availability indirectly influences interest in buying porang rice through perceived behavioral control. Recommendations for manufacturers' marketing strategies include providing information about low calories and high fiber on their packaging and promotional media, expanding their partner network with retail stores that are frequently visited by the public, and maximizing sales using e-commerce.